2019
DOI: 10.3390/polym11061075
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Interfacial Loading Characteristics of Boron Nitride-Carbon Nanosheet Reinforced Polymer Nanocomposites

Abstract: The discovery of hybrid boron nitride–carbon (BN–C) nanostructures has triggered enormous research interest in the design and fabrication of new generation nanocomposites. The robust design of these nanocomposites for target applications requires their mechanical strength to be characterized with a wide range of factors. This article presents a comprehensive study, with the aid of molecular dynamics analysis, of the tensile loading mechanics of BN–C nanosheet reinforced polyethylene (PE) nanocomposites. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…For example, Young's modulus and tensile strength of polyacrylic acid (PAA) hydrogel (water content 70 wt.%) composites were increased by 244% and 57%, respectively, when 0.5 g L −1 BNNSs was added to the PAA hydrogel 112 . This excellent reinforcement 49,67,81,92,102,105,[108][109][110]112,113,132,140,152,156,183,233,236,[245][246][247][248][249] . Fig.…”
Section: Bnns-polymer Nanocomposite Properties Mechanical Propertiesmentioning
confidence: 83%
“…For example, Young's modulus and tensile strength of polyacrylic acid (PAA) hydrogel (water content 70 wt.%) composites were increased by 244% and 57%, respectively, when 0.5 g L −1 BNNSs was added to the PAA hydrogel 112 . This excellent reinforcement 49,67,81,92,102,105,[108][109][110]112,113,132,140,152,156,183,233,236,[245][246][247][248][249] . Fig.…”
Section: Bnns-polymer Nanocomposite Properties Mechanical Propertiesmentioning
confidence: 83%
“…The mechanical properties of polymer nano composites are highly dependent on the NPs dimension, applied load, and NPs/polymer matrix interfacial bonding (Tran et al 2008). The interfacial bonding is crucial for evaluating mechanical load transfer from polymer matrix to NPs (Vijayaraghavan and Zhang 2019). Notably, the interfacial adhesion is the primary determinant of the toughness and strength of the composites.…”
Section: Influence Of Interface Between Nanoparticles and Natural Fib...mentioning
confidence: 99%
“…They analyzed the mechanical properties of composites such as hardness, tensile, bending and impact strength. Venkatesh Vijayaraghavan et al [6] presented a comprehensive study with the help of molecular dynamic analysis of tensile loading mechanics of polyethylene (PE) nano composites reinforced with BN-C nano layers. They observed that the geometry and lattice arrangement of BN -C nano layers affect the tensile load properties of nano…”
Section: Introductionmentioning
confidence: 99%